دور الصفحات الفايسبوكية في الترويج للمنتوجات المنزلية دراسة تحليلية على عينة من الصفحات الفايسبوكية - عايش مباركة; بوزيان نسرين (My University, 2022)
Study summary: The study aims to identify the role of Facebook pages in promoting home products by knowing the nature of promotional topics in the study sample publications, identifying the nature of multimedia and persuasive solicitations employed and how followers interact with publications. Intentionality of the Facebook pages, which amounted to four pages and 16 publications. The study reached a number of results, the most important of which are: - Promotional topics on the page owner's posts received great attention from followers. The publications employed persuasive and emotional persuasion. - The owner of the Facebook page used a mixture of more than one language in his publications. - The audience's interaction with the Facebook page and the content it provides, as most of its publications were interactive in terms of reactions, likes, comments and shares. ----------------------------------- ملخص الدراسة: تهدف الدراسة إلى التعرف على دور صفحات الفيسبوك في الترويج للمنتجات المنزلية من خلال معرفة طبيعة المواضيع الترويجية في منشورات عينة الدراسة، والتعرف على طبيعة الوسائط المتعددة والرسائل الإقناعية المستخدمة، وكيفية تفاعل المتابعين مع المنشورات. وتوصلت الدراسة إلى عدد من النتائج، أهمها: - حظيت المواضيع الترويجية في منشورات صاحب الصفحة باهتمام كبير من المتابعين. - وظفت المنشورات أسلوبي الإقناع الإقناعي والعاطفي. - استخدم صاحب صفحة الفيسبوك مزيجًا من أكثر من لغة في منشوراته. - تفاعل الجمهور مع صفحة الفيسبوك والمحتوى الذي تقدمه، حيث اتسمت معظم منشوراتها بالتفاعلية من حيث التفاعلات والإعجابات والتعليقات والمشاركات.
Keywords: دور الصفحات الفايسبوكية، الترويج، المنتوجات المنزلية، الصفحات الفايسبوكية